Analisa Aplikasi E-Commerce Pada Toko Maju Jaya Komputer - Rama Santo; Djumadi Sastro Wiyono (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2023)
Maju Jaya shop which is located on Jl. Fatmawati Raya No. 74 Semarang City. Toko Maju Jaya itself is engaged in selling computers and accessories. Toko Maju Jaya itself has 7 employees who work as a technician 1 person, marketing 2 people, inventory / warehouse 1 person, shop 1 person and administration 1 person. So far, customers come from the city of Semarang and its surroundings, such as Kendal, Pati, Jepara, Kudus, Demak, Ambarawa, Ungaran and Purwodadi